RF AND ANTI-CCP POSITIF IN ANKYLOSING SPONDYLITIS(AS) PATIENT WITH RHEUMATOID ARTHRITIS(RA): TRUE OR FALSE POSITIVE? TRUE OR FALSE POSITIVE? - Margalin, Brilliant; Aryati, Aryati; Yuliasih, Yuliasih; R Raharjo, Paulus (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
Ankylosing Spondylitis (AS) and Rheumatoid Arthritis (RA) are different autoimmune arthritis diseases but have overlapping clinical manifestations. Rheumatoid Factor (RF) and Anti-Cyclic-Citrulinated-Peptide (anti-CCP) serological examinations have an important role because they are seropositive in RA and seronegative in AS. This case report is interesting because it discusses a patient with AS who was unexpectedly negative for HLA-B27, positive for RF and anti-CCP, raising doubts about clinical and laboratory discrepancies. Patients with AS and RA disease can occur simultaneously, although it is very rare. This case report analyzes the diagnostic role of RF and Anti-CCP examinations, whether they are true positive or false positive.